Small Firms, Big Impact - Lilja Berefelt,Daniel; Christell,Louise (2025)
Title: Small Firms, Big Impact: Investigating ESG and Sustainability Strategy in SMEs Seminar Date: 2025-06-04 Course: BUSN09, Degree project in International Strategic Management Authors: Louise Christell & Daniel Lilja Supervisor: Merle Jacob Keywords: SME, Corporate sustainability, ESG, Strategy, Trade-off, Stakeholder management Purpose: The primary purpose of this study is to explore and understand the factors that drive strategic initiatives in sustainability and ESG in small and medium-sized enterprises (SMEs) in Sweden. Examining underlying drivers, trade-offs, strategic decision-making and stakeholder demands. Methodology: This study adopts a qualitative abductive approach to compare multiple cases. The data collection was based on eight semi-structured interviews with corporate executives taking strategic decisions in sustainability, from five different case companies in the process and material-based manufacturing sector. Theoretical Perspective: This study is based on the Trade-off theory and Stakeholder theory, coupled with concepts such as sustainability, ESG, and strategy in a VUCA world. It covers how SMEs manage conflicting demands, allocate resources, and approach corporate sustainability standards. Empirical Foundation: The empirical findings of this study are based on comparison between five case companies and consist of detailed insights and perspectives gathered from semi-structured interviews with corporate professionals, as well as the authors interpretations of both the collected data and existing literature on the topic. Themes highlighted are ESG and sustainability understanding in SMEs, formalization and structuring of stakeholder management, the alignment of sustainability with operational and financial priorities, and balancing short-term and long-term sustainability goals. Conclusion: The findings of this study concludes that despite limited resources and increasing external pressures, Swedish production SMEs demonstrate a proactive and strategic approach to ESG and sustainability. They tend to align sustainability initiatives with business objectives, operational realities, and stakeholder expectations. The results provide a nuanced understanding of the trade-offs, motivations, stakeholder management initiatives and adaptive strategies shaping ESG work in resource-constrained settings that SMEs operate in.
Keywords: SME; Corporate sustainability; ESG; Strategy; Trade-off; Stakeholder management